Anti-rabies antibodies serological investigation from dogs of a rural area in São Paulo state – Brazil - Peres, M. G.; Bacchiega, T. S.; Martorelli, L. F. A.; Kataoka, A. P. A. G.; Vicente, A. F.; Apollinario, C. M.; Allendorf, S. D.; Antunes, J. M. A. P.; Megid, J. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies is one of the most important zoonoses, with fatal prognosis in almost 100% of cases. It is estimated that every 10 to 15 minutes one person dies from a rabies virus infection and 1000 people receive post-exposure treatment by hour in the world. Dogs are the main transmitters to man by bite, so it is estimated that approximately 55,000 cases of human rabies in the world are caused by dog viral variant. The main preventive measure of human cases is the rabies vaccination campaign of dogs and cats, which was responsible by the decrease of dog and consequently human rabies number . The last human rabies case caused by canine rabies virus in the state of São Paulo occurred in 1997 and in 1998 the last case canine rabies. In this context the present work aimed to evaluate the effectiveness of protective vaccination of dogs from rural farms in the county of Anhembi – SP, after two years without being immunized against rabies with a vaccine campaign. During 2011 an epidemiological questionnaire was applied to 22 farms to collect data about the health of animals and hygienic handling of property. One hundred percent of dog’s owners declared that their dogs only received anti-rabies vaccine during public campaing that was stopped two years before. Fifty one dogs blood samples were collected by jugular vein puncture. The blood collection tube was centrifuged and the serum stored at -20 ° C. Sera were tested for neutralization in cell culture for the determination of neutralizing antibodies to rabies virus by rapid method focus inhibition of fluorescence (RIFFT). Of the 51 analyzed dogs, 68% presented antirabies antibodies titers above 0.5 UI/ml, indicating that they are still protected but on the other hand 32% of analyzed population was detected unprotected and therefore susceptible to infection. Our results agree with literature data that indicates that rabies vaccine induce immunity longer than one two years and consider the revaccination every three years but at the same time demonstrate that a percentage of the animals don’t mantain protective titers after two years indicating that the revaccination protocol must be carefully evaluated considering the epidemiological situation.